Adult neurodevelopmental services in Singapore: A sociodemographic and clinical profile at a tertiary psychiatric hospital. (14th April 2020) - Moon, James Patrick; Tan, Ho Teck; Lam, Kwok Foong; Lim, Jan Mei; Cheak, Ching Cheng; Wei, Ker‐Chiah; Sajith, Sreedharan Geetha; Chai, Suet Bin; Tan, Giles Ming Yee
Abstract: Introduction: The Adult Neurodevelopmental Service in Singapore is the first service of its kind in South‐East Asia for adults with intellectual disability (ID) and/or autism spectrum disorder (ASD). However, few studies have documented and compared the sociodemographic characteristics and clinical needs of this subpopulation group. Methods: Initial assessments conducted from 1 January 2015 to 31 December 2016 were retrospectively reviewed for this descriptive study. Results: A total of 272 patients were included in the study (mean age 28.3 ± 11.5; 200 males, 72 females). Adults with ID comprised the largest percentage (52.9%), followed by those with ASD (30.2%), and then those with co‐occurring ASD and ID (16.9%). The ASD subgroup had the highest proportion of individuals with employment, postsecondary school education, functional capabilities, and a psychiatric disorder. In comparison, adults with only ID and adults with co‐occurring ASD and ID shared similar lower levels of education and employment, and had a higher proportion of individuals with epilepsy and aggressive behavior. Discussion: In this study, adults with ASD had a unique social profile with different clinical needs compared to adults with only ID or to adults with co‐occurring ASD and ID. Adults with only ID and those with co‐occurring ASD shared many of the same social characteristics and high clinical needs. The analysis of these profiles will be useful in developing services that better meet the needs of this complex group.